The language and intercultural communication reader - Hua, Zhu, 1970-
Language is key to understanding culture, and culture is an essential part of studying language. This reader focuses on the interplay between Language and Intercultural Communication. Reflecting the international nature of the field, this reader covers a wide range of language and cultural contexts: Arabic, Chinese, English (British, American, Australian and South African), Greek, Hebrew, Japanese, Samoan and Spanish. Divided into six parts, it covers: Culture, language and thought; Cultural approaches to discourse and pragmatics; Communication patterns across cultures; Teaching and learning cultural variations of language use; Interculturality and Intercultural Communication in professional contexts. With readings by eminent authorities in the field as well as cutting-edge materials representing current developments, the book explores the breadth and depth of the subject as well as providing an essential overview for both students and researchers. Each part begins with a clear and comprehensive introduction, and is enhanced by discussion questions, study activities and further reading sections. Alongside a comprehensive Resource List, detailing important reference books, journals, organisations and websites and an annotated Glossary of key terms, the final section offers advice on how to carry out research in Language and Intercultural Communication.